How researchers could benefit from working in new ways - CGIAR Research Program on Climate Change, Agriculture and Food Security (2011)
Interview with Bill Clark from Harvard University. Filmed at The Conference on Climate Change, Agriculture, and Food Security, 4 May 2010, Nairobi, Kenya